Sensory-to-Motor Overflow: Cooling Foot Soles Impedes Squat Jump Performance - Caminita, Mia; Garcia, Gina L.; Kwon, Hyun Joon; Miller, Ross H.; Shim, Jae Kun (Frontiers in Human Neuroscience, 2020)
Evidence from recent studies on animals and humans suggest that neural overflow from the primary sensory cortex (S1) to the primary motor cortex (M1) may play a critical role in motor control. However, it is unclear if whole-body maximal motor tasks are also governed by this mechanism. Maximum vertical squat jumps were performed by fifteen young adults before cooling, then immediately following a 15-minute cooling period using an ice-water bath for the foot soles, and finally immediately following a 15-minute period of natural recovery from cooling. Jump heights were, on average, 3.1cm lower immediately following cooling compared to before cooling (p=3.39 x 10-8) and 1.9cm lower following natural recovery from cooling (p=0.00124). Average vertical ground reaction force was also lower by 78.2N in the condition immediately following cooling compared to before cooling (p=8.1 x 10-5) and 56.7N lower following natural recovery from cooling (p=0.0043). The current study supports the S1-to-M1 overflow mechanism in a whole-body dynamic jump.